Annual Plan 1977-78 Administration of the Union Territory of Lakshadweep - Planning Commission (Planning Commission, 1977)
The Fifth Five Year Plan 1974-79 was launched in April 1 974. The Planning Commission has fixed the size of the Fifth Plan at Rs.622.73 lakhs which is more than three times of the size of the Fourth Five Year Plan. The actual expenditure for 1974-75 and 1975-76 was Rs.73.29 lakhs and Rs.72.92 lakhs respectively and the total outlay for 1976-77 Rs 30 lakhs.
Administration of the Union Territory of Lakshadweep